Effectiveness of Regional Supervisory Boards In Supervision and Guidance of The Code of Ethics For Notaries In Pekanbaru City - Heldawati, Eka Putri; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Article 70 and 71 of the Notary Law (UUJN) authorizes the Regional Supervisory Council (MPD) to supervise the implementation of the duties and authorities of Notaries, including holding hearings for violations of the code of ethics, examining protocols, granting leave permits, appointing substitute Notaries, and receiving reports of violations. This study aims to analyze: 1) The effectiveness of the Regional Supervisory Council (MPD) of Pekanbaru City in carrying out its supervisory and development functions for Notaries has not been effective. 2) What obstacles are faced by the Regional Supervisory Council (MPD) in carrying out its duties and authorities in Pekanbaru City. The approach method in this study is the Structural approach and economic analysis of law. This type of research uses empirical law. The types and sources of data in this study are primary data obtained through interviews and observations. The analysis in this study is descriptive qualitative. The results of the study indicate that the Regional Supervisory Council (MPD) has played an active role in following up on public complaints and carrying out its functions in accordance with legal provisions, but the effectiveness of the implementation of MPD supervision has not been optimal because it faces several obstacles such as reporting mechanisms, limited human resources, inconsistent sanctions and social barriers between Notaries, to increase the effectiveness of MPD supervision it is recommended to develop a more transparent and easily accessible reporting system, and strengthen direct supervision through routine inspections. In addition, the application of stricter and more consistent sanctions against violations committed by Notaries must be enforced fairly and effectively.Keywords: Effectiveness; Code of Ethics; Guidance; Notary; Regional Supervisory Board; Supervision.